Six Short Plays - Galsworthy, John, 1867-1933 (Salt Lake City, UT : Project Gutenberg, 2004)
"Six Short Plays" by John Galsworthy is a collection of theatrical works crafted in the early 20th century. This compilation delves into a variety of human experiences and social dynamics, exploring themes of morality, the complexities of relationships, and societal expectations through different characters and settings. Each play encapsulates intense emotions and thought-provoking dialogues that reflect Galsworthy's keen insight into human nature. The opening portion of the first play, "The First and The Last," introduces us to brothers Keith and Larry Darrant. In a tense atmosphere, Larry confesses to Keith that he has accidentally killed a man during a struggle while defending a woman he loves, Wanda. The scene unfolds with a swirl of anxious dialogue as Larry grapples with guilt and panic, seeking guidance from Keith, who is on the brink of a legal career and is drawn into a moral quandary. Simultaneously supportive and incredulous, Keith's reactions set the tone for a dramatic conflict that revolves around loyalty, love, and the consequences of one's actions, laying the groundwork for further exploration of these themes in the ensuing drama. (This is an automatically generated summary.)
The first and the last -- The little man -- Hall-marked -- Defeat -- The sun -- Punch and go.
Release date is 2004-09-26
Produced by David Widger
Keywords: England -- Drama